Teaching retarded women a clothing selection skill using community norms. - Nutter, D (1978)
Five institutionalized retarded women were taught a clothing selection skill to coincide with popular fashion. Normative data concerning popular styles of color-coordinated clothing were collected through observations of women's apparel in a local community. Using a puzzle simulation of a woman with alternative pieces of colored clothing, color coordination training was conducted using modelling, instructions, practice, praise, and feedback to teach popular selections of color combinations. A generalization training component with actual clothing was also included. Training was accompanied by large increases in percentage of popular color selections with the puzzle and actual clothing. The increases maintained over a seven- to 14-week followup period. Time efficiency measures supported the use of the simulation procedure as opposed to total reliance on actual clothing. The results underscore the utility of local norms in community preparation programs and the efficacy of instructional procedures for severely and profoundly retarded persons as part of their participation in the deinstitutionalization movement.